Campbell University Student-Run Free Clinic: Osteopathic Medical Care for the Rural Underserved - Kathryn Taylor; Elizabeth Willis; Jordan Hitchens; Daniel Moses; Jeffrey Pennings; Phillip Deal; Anthony Parker; James Hooper; Mark Lorenzini; Richard Dobson; Paul Pikman (Journal of Student-Run Clinics, 2016)
Based at the Campbell University School of Osteopathic Medicine, the Campbell University Student-Run Free Clinic (CUFC) is an interprofessional effort to address the medical needs of the rural underserved population in Harnett County of central North Carolina. Although osteopathic physicians have historically been more likely to practice primary care, particularly in rural settings, than their allopathic counterparts, osteopathic medical schools are often omitted in the current research and literature on student-run free clinics. This report details the development of the CUFC, including a basic needs assessment, staffing and recruitment, resource identification, clinic operations, electronic medical record, and quality assessment and research. The CUFC demonstrates a working model for a free clinic based at an osteopathic medical school in a rural underserved area that can potentially be replicated in other regions.